Structural, Optical and Spectral Behaviour of InAs-based Quantum Dot Heterostructures Applications for High-performance Infrared Photodetectors - Sengupta, Saumya (Springer Singapore, 2018)
This book explores the effects of growth pause or ripening time on the properties of quantum dots(QDs). It covers the effects of post-growth rapid thermal annealing (RTA) treatment on properties of single layer QDs. The effects of post-growth rapid thermal annealing (RTA) treatment on properties of single layer QDs are discussed. The book offers insight into InAs/GaAs bilayer QD heterostructures with very thin spacer layers and discusses minimum spacer thickness required to grow electronically coupled bilayer QD heterostructures. These techniques make bilayer QD heterostructures a better choice over the single layer and uncoupled multilayer QD heterostructure. Finally, the book discusses sub-monolayer (SML) growth technique to grow QDs. This recent technique has been proven to improve the device performance significantly. The contents of this monograph will prove useful to researchers and professionals alike. .